Gad1 knock-out rats exhibit abundant spike-wave discharges in EEG, exacerbated with valproate treatment - Liu, Dongyu; Fujihara, Kazuyuki; Yanagawa, Yuchio; Mushiake, Hajime; Ohshiro, Tomokazu (Frontiers in Neurology, 2023)
Essential roles of GABAergic inhibition to prevent seizures and epilepsy have been suggested in human and model animals. In this study, we report that rats deficient for the gene encoding glutamate decarboxylase 1 (GAD1), a GABA synthesizing enzyme, exhibit abundant spike-wave discharges (SWDs) in EEG from early ages, whose close relationship with absence seizure has been suggested in many studies. To examine if SWDs in these rats represent an epileptic brain activity, we conducted a behavioral experiment to interrupt SWDs by external sensory stimuli while monitoring EEG, and found that a modest number of the SWDs in Gad1 rats were resistant to the interruption, indicating an epileptic nature of the paroxysmal brain activity. We further demonstrate that valproate treatment rather worsened the symptom in Gad1 rats and that the change in the GABA level in the reticular thalamic nuclei (RTN) was correlated with the severity of the symptom. Overall, our results suggest two opposing roles of GABA in SWD generation: suppression and enhancement of SWDs. To account for these contradictory roles, we propose a model in which GABA produced by GAD1 in the RTN neurons is released extrasynaptically and mediates intra-RTN inhibition.